Utilization of Information and Communication Technologies (ICT) in English Learning to Improve Language Literacy - Purwanto, M Bambang; Yuliana, Yuliana; Agustin, Ariya; Despita, Despita (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study examines the use of Information and Communication Technologies (ICT) in English language learning as a means to enhance students' language literacy in Indonesia, particularly in response to the low literacy levels reported by PISA. The primary challenge addressed is the lack of understanding and ability among students to evaluate texts, largely due to limited access to interactive and practical learning resources. The purpose of this research is to explore the impact of ICT on improving various aspects of language literacy, including reading comprehension, information connection, and text evaluation skills. Utilizing a mixed-methods approach, data were collected through questionnaires, interviews, and documentation. The findings reveal that ICT usage significantly improves students’ language literacy, especially in text comprehension and analysis. Based on previous studies and current technological applications, ICT has proven to be effective in enhancing both English language learning and literacy development. With greater accessibility, increased interactivity, and the support of innovative tools, ICT offers a more modern and effective alternative to traditional teaching methods. In conclusion, despite challenges related to access and distribution, ICT plays a positive and influential role in supporting the development of students’ language literacy.